2021
DOI: 10.3856/vol49-issue1-fulltext-2512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio parahaemolyticus strains and evaluation of shrimp cultivation conditions in a farm at the northwestern of Mexico, as risk predictors for its adaptation and dissemination

Abstract: Vibrio parahaemolyticus is recognized as a human pathogen as well as the causative agent of vibriosis in shrimp. This study determined the pathogenic, antimicrobial, and biotic potential of V. parahaemolyticus isolated from white shrimp (Penaeus vannamei) and seawater on a northwestern Mexico farm. A total of 140 samples were randomly collected, including juvenile organisms (n = 120) and seawater (n = 20). The pH, salinity, and biota of the ponds were used to correlate with bacterium presence. The strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…The few strains of Vibrio parahaemolyticus species are human pathogens, causing gastroenteritis(Broberg et al 2012) it can be inhibited by Spirulina platensis mediated silver nanoparticles. Overall, 55.7% and 58.3% of Vibrio parahaemolyticus are present in our study area Cuddalore and in the Nagappattinam district which is higher than the 20 percent recorded byGámez- Bayardo et al 2021. Also, Silvester et al (2015 reported 71.6% in the Cochin estuary and 53.3% in the shrimp farm Biju and Gunalan (2016).…”
contrasting
confidence: 46%
“…The few strains of Vibrio parahaemolyticus species are human pathogens, causing gastroenteritis(Broberg et al 2012) it can be inhibited by Spirulina platensis mediated silver nanoparticles. Overall, 55.7% and 58.3% of Vibrio parahaemolyticus are present in our study area Cuddalore and in the Nagappattinam district which is higher than the 20 percent recorded byGámez- Bayardo et al 2021. Also, Silvester et al (2015 reported 71.6% in the Cochin estuary and 53.3% in the shrimp farm Biju and Gunalan (2016).…”
contrasting
confidence: 46%
“…Furthermore, understanding the growth pattern of Vibrio is essential to develop effective control measures as a preventive measure for crustacea contamination (Letchumanan et al, 2014). Gámez-Bayardo et al (2021) stated that identifying the factors contributing to Vibrio's growth can help improve food safety. In aquaculture, characterizing the growth of Vibrio can assist in developing effective disease management strategies (de Souza Valente & Wan, 2021).…”
Section: Introductionmentioning
confidence: 99%